Inovasi Kurikulum PAI untuk Meningkatkan Kompetensi Mahasiswa - zaini, muhammad (Ta'allum: Jurnal Pendidikan Islam, 2019)
Innovation is defined as renewal dealing with a change or an improvement. A change is shifting of position or situation that enables to lead to significant improvement. Practically curriculum is changed because of some factors, forexample science and technological development. There is a possibility that the advantages on pre-determined or pre-expected  of curriculum change can be wrong. A curriculum change in a very short period in certain case is supposed as a failure, however it is also believed as an efford to  achieve improvement. A curriculum renewal involves some components or some factors. A curriculum change cannot be successful without being equipped by those supported components system. A change that is partial in nature automatically wastes energy, time, fund, and also power. Moreover, a curriculum change which is focused more on a curriculum itself and it ignores other aspects; such as teacher/lecturer, student, method, media fund, etc will be potential to be fail.  That is why it needs a serious consideration and plausible reasons with a total eagerness and involvement of  components of educational system, so it can enhance students’ competencies.